2010
DOI: 10.1111/j.1365-2591.2010.01809.x
|View full text |Cite
|
Sign up to set email alerts
|

Viability of human periodontal ligament fibroblasts in milk, Hank’s balanced salt solution and coconut water as storage media

Abstract: Skimmed and whole milk had the greatest capacity to maintain PDLF viability when compared with natural coconut water, HBSS, Save, industrialized coconut water and tap water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
85
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(102 citation statements)
references
References 24 publications
12
85
1
3
Order By: Relevance
“…Milk is a proven storage medium for avulsed teeth (6,8,11), but cell culture studies have shown that its effectiveness decreases over time (6)(7)(8), probably because the drop in its pH creates an unsuitable environment for cell survival (3). Thus, it was hypothesized that the renewal of milk for storing the avulsed tooth could prevent the drop in its pH.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Milk is a proven storage medium for avulsed teeth (6,8,11), but cell culture studies have shown that its effectiveness decreases over time (6)(7)(8), probably because the drop in its pH creates an unsuitable environment for cell survival (3). Thus, it was hypothesized that the renewal of milk for storing the avulsed tooth could prevent the drop in its pH.…”
Section: Discussionmentioning
confidence: 99%
“…While some demonstrated effectiveness for only up to 3 h (15,19) or 6 h (4), other showed effectiveness for 24 h (6,17,(20)(21)(22) or for up to 48 h (7,8). When culture plates were maintained at 20 °C and 37 °C, milk was the best storage medium for up to 48 and 24 h, respectively (7).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The agents used to neutralize the pH of coconut water must be stable over time and have no negative influence on the osmolarity. Another important factor is the possible difference regarding properties of natural versus industrialized coconut water, which may influence the final results 19 .…”
Section: Introductionmentioning
confidence: 99%